إجراءات التقاضي في دعاوى الأحوال الشخصية - أحمد, د. عطا عبدالحكيم; ش, د. آكو فاتح حمه ره (Sulaimani Journal for Humanities, 2023)
The rules of the Civil Procedures Law permitted the cessation of litigation in civil cases without a ruling by invalidating the lawsuit petition, whether as a procedural penalty or at the request of the plaintiff. This law also states the inevitability of appeal periods and the inadmissibility of exceeding them, and expiration of this period leads to the lapse of the right to appeal. And it states to send the files of some claims and pleas to the Court of Cassation if its rulings are not plead by the parties in order to do cassational audits on it. Among these ; the claims about annulment of marriage contract, because of its relation to permissiveness (Halaal) and inviolability. In this research, we have dealt with the suitability of the rules of annulment of the lawsuit petition and the rule of inevitability of appeal periods in personal status law cases. We have also defined other personal status law cases related to permissiveness (Halaal) and inviolability, and that their provisions must be included by automatic cassation, just as they are in the case of annulment of marriage contract